EVALUASI FUNGSI KERJA PETUGAS ASSEMBLING DI RUMAH SAKIT PUSAT PERTAMINA TAHUN 2020 - Elsa Mayori; Feby Erawantini; M. Choirur Roziqin; Djasmanto Djasmanto (Politeknik Negeri Jember, 2021)
Based on a preliminary study, the implementation of the medical record assembling at Pertamina CentralHospital was still inappropriate. The return of the medical record file from the inpatient has been delayed,more than 2x24 hours, the medical record file was not 100% complete. The purpose of this study was toevaluate the function of assembling work at Pertamina Central Hospital with 5M management elementsconsisting of man, money, method, machine, material. This type of research was qualitative research withdata collection methods were interview, observation, and documentation. The subject of this research wasthe assembling officer. The results showed that there were problems with man, method, and materialvariables. Man variable, the lack of staff's knowledge about understanding the importance of medicalrecords. Method variables, assembling SOP in Pertamina Central Hospital was not in accordance with thetheory because quantitative analysis of medical record file still not exist. Material variable, medical recordfile wais not 100% complete in the authentication aspect. The solution is to include medical records officersin training activities about medical records, assembling workload evaluation, assembling Standard OperatingProcedures shall be added to control medical records incompleteness (quantitative analysis) and create theKLPCM form to find any deficiency or incomplete medical record file, that will have an impact for improvingthe quality of the medical record.